EVOLUTIONARY ANALYSIS OF SPORTS FACILITIES (Physical Culture and Sport: Scientific Perspective, 2025)
In the modern world, physical education and sports provide an opportunity to change the sedentary lifestyle of people. Physical education and sports are an important source of forming a healthy and strong nation, and this is a reserve for improving productive forces with ensuring high labor productivity. Full-fledged physical education and sports activities are impossible without special facilities, which are sports facilities.Sports facilities of different stages were not only a place for holding physical education and sports events, but also religious and cultural buildings.The possible influences of different historical periods on the transformation of sports facilities require a deeper analysis.The purpose of the study is to characterize the evolution of sports facilities in accordance with the periods of historical development of society.This study used a set of interrelated research methods, namely: analysis, synthesis and generalization of scientific information on the research problem, educational and methodological literature and Internet sources.Sports facility - real estate intended for physical culture and sports.In the ancient world, sports facilities were not only a place of competition, but also cultural and social centers. They reflected the ideal of man of that time - a combination of strength, beauty and spirituality. The architectural masterpieces of ancient gymnasiums, stadiums, amphitheaters and baths became the basis for the development of sports infrastructure in subsequent eras.Sports facilities of the Middle Ages were formed around knightly culture and folk games and were mainly of a military-entertainment nature, were less monumental than ancient ones, but played an important role in socialization, education and preparation for battle.Sports facilities have become an important component of the development of physical culture and sports in modern times. They reflect the level of socio-economic development of society, technical progress, cultural values and the mass nature of sports. If in the Middle Ages the sites for knightly tournaments and folk games prevailed, then starting from the 18th century. specialized complexes gradually appear that meet the requirements of the sport.The development of sports facilities in modern times is characterized by a combination of scale, technologicality, architectural uniqueness and environmental friendliness. Stadiums and arenas have become not only venues for competitions, but also centers of culture, leisure and communication, performing an important social and economic role in society.
Keywords: sports facility; periodization of history